Awareness of Eye Health and Disease in the population of hilly region of Nepal: A Community Based Study - Belbase, U.; Subedi, A.; Sharma, S.; Prajapati, S.; Budhathoki, S.; Khanal, P.; Bhattarai, S. (Devdaha Medical Journal, 2024)
Background: Ocular diseases, such as, cataracts, glaucoma, and refractive errors, can lead to significant vision impairment or blindness if left unaddressed, affecting individuals’ quality of life and limiting their daily activities. In rural communities with limited healthcare access, awareness about these conditions is often insufficient, resulting in delayed diagnosis and missed opportunities for early intervention. This study explores the level of eye health awareness in such a community, aiming to uncover knowledge gaps and common misconceptions. The findings are intended to guide targeted health interventions and educational efforts, empowering residents to seek timely eye care and reduce the impact of preventable visual impairment. Methods: A cross-sectional survey was carried out from 6th Shrawan to 11th Shrawan 2079, involving 352 participants (199 males, 153 females). Data were collected using structured interviews focusing on awareness of eye diseases, causes, and preferred treatment options. Results: The study revealed that 57.7% of participants responded blurring of vision as eye illness. However, only 14.8% recognized all common eye conditions. Cataract awareness was moderate, with 45.2% identifying age as the leading cause. However, 35.2% were unaware of any causes of cataract. Glaucoma awareness was low, with 69.6% being unfamiliar with the condition, and 75.6% unaware that vision loss due to glaucoma is irreversible. Awareness of strabismus was relatively high (69%), though misconceptions regarding its causes still persisted. Conclusion: The findings indicate a significant gap in the community’s awareness of eye health, particularly regarding cataract and glaucoma. This underscores the need for targeted educational programs to improve understanding and encourage early detection and treatment.